Folate contents in insects as promising food components quantified by stable isotope dilution - Weber, Nadine; Kouřimská, Lenka; Kulma, Martin; Petříčková, Dora; Seufert, Franziska; Rychlik, Michael (Frontiers in Nutrition, 2022)
Concerning the increasing population eatable insects are of growing interest due to several advantages such as sustainable production and as a source of high-quality nutrients. One of the less studied nutrients in the context of insects are folates which play an important role in the human metabolism. In the following it is described how six different insect species are reared and extracted for five common folate vitamers by high performance liquid chromatography interfaced with a tandem mass spectrometry (LC-MS/MS). For this purpose, house crickets (Acheta domesticus - adults), Jamaican field crickets (Gryllus assimilis - adults), discoid cockroaches (Blaberus discoidalis - nymphs), migratory locusts (Locusta migratoria - adults), mealworms (Tenebrio molitor) and lesser mealworms (Alphitobius diaperinus) were investigated. The total folate content differs between 59.1 ±6.50 and 143 ±11.1 µg/100 g. Also, the feed, which was adapted to the needs of the insects and differ for some species, were extracted for their total folate content. The four different feed compositions (rapeseed, chicken feed, bramble leaves and a mix of chicken feed, wheat bran and carrot/apples) showed a folate content about 100 µg/100 g except for hay, where the content was 300 µg/100 g. In general, the insect’s folate content is comparable to other food and seems to be a promising source of folates. However, the amount of consumption needed to meet the requirement must also be considered. Moreover, the effect of different influencing factors is not yet entirely clear and needs further investigation.